POLYMORPHISM IN STEROID 11-BETA-HYDROXYLASE GENE EFFECTS ON MILK FAT CONTENT IN SAHIWAL CATTLE - S. Manzoor; A. Nadeem; J. Maryam; M. E. Babar; T. Hussain; Z. I. Rajput (Journal of Animal and Plant Sciences, 2018)
Genetic improvements of livestock is mainly depends on selective breeding of animal with its superior phenotypes. Identification and use of molecular markers for production and economical traits has been ensured the better health and productivity of cattle. Cytochrome P450, family 11, subfamily b, polypeptide 1 (CYP11B1) gene is a candidate affecting milk composition traits as adjacently located to marker ILSTS039 that has been linked with milk yield and milk component. The current study was performed to characterize the CYP11B1 gene in Sahiwal cattle. The overall sequence variation across the CYP11B1 locus is high and total thirteen variations were observed in Sahiwal cattle. Association test was executed against all variations obeying Hardy Weinberg Equilibrium (HWE) and found non-significant except g.1305935 (T401M) that was found associated with milk fat percentage in Sahiwal cattle population. It is illustrated that CYP11B1 gene has an influential dairy potentials in cattle can also be incorporated into genetic evaluation.
Keywords: CYP11B1; SNPs; Association; Milk fat percentage; Sahiwal cattle